Feeling states of people experiencing depression, anxiety, or comorbid depression and anxiety symptoms during a multi-day charity cycling ride: An ecological momentary assessment study. (March 2020) - Rebar, Amanda L.; Stanton, Rob; Wells, Ruth; Steel, Zachary; Rosenbaum, Simon
Abstract: Objective: Regular exercise has substantial benefits for mental health. The way people feel during exercise impacts motivation. This study investigated whether experiencing depression, anxiety or comorbid depression and anxiety symptoms impacted feeling state responses throughout a charity cycling ride. Design: To achieve this aim, we conducted an ecological momentary assessment study of feeling states (via Pleasant and Negative Affect Schedule items) across a multi-day cause-based cycling event. Method: Multivariate and univariate generalized linear mixed models was applied to test how affective and self-conscious emotional experiences changed across time and whether feeling state change differed between people experiencing depression, anxiety, or comorbid depression and anxiety symptoms. Results: For people experiencing depression symptoms, positive feelings decreased and negative feelings increased throughout the event. People experiencing anxiety symptoms had initially elevated negative feeling states that decreased across the event. For people experiencing comorbid depression and anxiety symptoms, changes in pride mirrored that of people experiencing only depression symptoms (decrease from initially high levels); whereas changes in guilt mirrored that of people experiencing only anxiety symptoms (initially high levels that decreased throughout event). Conclusions: These findings demonstrate that depression and anxiety symptoms put people at risk for having negative affective and emotional experiences during exercise events and that these effects are further complicated when depression and anxiety symptoms co-occur. Exercise events and interventions must consider how to mitigate the potentially demotivating impacts that negative affective judgments can have on motivation for future exercise participation of people experiencing depression and/or anxiety symptoms. Highlights: Depression and anxiety symptoms impact feelings during multi-day cycle event. Depression symptoms led to less positive and more negative feelings across the event. Experiencing anxiety resulted in lower levels of positive feeling states initially. The negative impact of anxiety on positive feelings reduced across the event. Comorbid depression and anxiety led to different pride and guilt reactions.